Thermal inactivation and chaperonin-mediated renaturation of mitochondrial aspartate aminotransferase. - Lawton, J M (1998)
Mitochondrial aspartate aminotransferase is inactivated irreversibly on heating. The inactivated protein aggregates, but aggregation is prevented by the presence of the chaperonin 60 from Escherichia coli (GroEL). The chaperonin increases the rate of thermal inactivation in the temperature range 55-65 degrees C but not at lower temperatures. It has previously been shown [Twomey and Doonan (1997) Biochim. Biophys. Acta 1342, 37-44] that the enzyme switches to a modified, but catalytically active, conformation at approx. 55-60 degrees C and the present results show that this conformation is recognized by and binds to GroEL. The thermally inactivated protein can be released from GroEL in an active form by the addition of chaperonin 10 from E. coli (GroES)/ATP, showing that inactivation is not the result of irreversible chemical changes. These results suggest that the irreversibility of thermal inactivation is due to the formation of an altered conformation with a high kinetic barrier to refolding rather than to any covalent changes. In the absence of chaperonin the unfolded molecules aggregate but this is a consequence, rather than the cause, of irreversible inactivation.